Search frictions on product and labor markets: money in the matching function - Etienne Lehmann; Bruno van der Linden (Institute for the Study of Labor (IZA), 2007)
This paper builds a macroeconomic model of equilibrium unemployment in which firms persistently face difficulties in selling their production and this affects their decisions to create jobs. Due to search-frictions on the product market, equilibrium unemployment is a U-shaped function of the ratio of total demand to total supply on this market. When prices are at their Competitive Search Equilibrium values, the unemployment rate is minimized. Yet, the Competitive Search Equilibrium is not efficient. Inflation is detrimental to unemployment.
urn:nbn:de:101:1-20080402563
Keywords: 330; Arbeitslosigkeit; Matching; Inflation; Gleichgewichtstheorie; Theorie der Arbeitslosigkeit; Arbeitsuche; Theorie